THE PORTRAYAL OF WOMEN’S AMBITIONS THROUGH THE CHARACTER OF NINA SAYERS IN BLACK SWAN - Aurel Pinkan Millenia; Agustin Diana Wardaningsih (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
Ambition is the energy expressed in active behaviour towards a goal or aspiration, carried out with persistence and a common struggle in the pursuit of success, achievement, and completion. The existence of different societal perspectives related to men's and women's ambitions raises negative stigmas that harm women. Therefore, film is present as an entertainment medium, and as a channel to convey messages to portray social reality, and to change the perspective. One of the films that depict women's ambitions is